Mesoporous silica loaded with calcitonin gene-related peptide antagonist and curcumin alleviate oxidative stress and inflammation in the sciatic nerve - Zhu, Yi; Zhang, Zhuoliang; Gao, Liangliang; Tian, Yue; Lu, Xinyu; Jiang, Yinhong; Su, Huibin; Gu, Chengyong; Shi, Chenghuan; Wei, Lei (Frontiers in Molecular Biosciences, 2025)
BackgroundNeuropathic pain (NP) is a kind of chronic pain that can lead to neurasthenia. The effectiveness of current drug treatment for NP is still unsatisfactory due to its side effects, addiction and withdrawal. In recent years, researchers have begun to develop nano-drug delivery systems for the diagnosis and treatment of NP diseases.MethodsWe developed a disulfide-bonded magnetic mesoporous silica dual-drug delivery system consisting of curcumin (Cur) and a calcitonin gene-related peptide (CGRP) antagonist (CGRPi), and characterized by electron microscopy, Dynamic Light Scattering (DLS), Zeta, specific surface area and pore size detection. At the cellular level, the biocompatibility of CGRPi@Cur@Fe3O4@mSiO2-PEG (FMCC) nanoparticles were tested by CCK-8 and dead/alive staining kit in BV2 cells; Inflammation levels and oxidative stress were measured by enzyme linked immunosorbent assay (ELISA) in lipopolysaccharide (LPS)-induced BV2 neuroinflammation model. In vivo, chronic constriction injury (CCI) model was constructed, and the effect of FMCC on pain behavior of CCI mice was detected by von Frey filaments test and thermal hyperalgesia; The effects of FMCC on the anti-inflammatory and oxidative stress of CCI were determined by pathological tests (HE and ROS staining), RT-PCR and ELISA.ResultsFMCC had good biocompatibility and could be taken up by BV2 cells. At the cellular level, FMCC could effectively reverse oxidative stress, inflammation and CGRP expression in LPS-induced neuroinflammation model in vitro. At the animal level, the mice with CCI were administered with FMCC, which effectively reduced oxidative stress and inflammation and sustained relief of neuropathic pain.ConclusionThis study provides a new approach for the treatment of neuropathic pain.